2013
DOI: 10.1088/1758-5082/5/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial PCL/PVA electrospun nanofibers: osseointegration enhancer and controlled drug release device

Abstract: The failure of prosthesis after total joint replacement is mainly due to dysfunctional osseointegration and implant infection. There is a critical need for orthopedic implants that promote rapid osseointegration and prevent bacterial colonization, particularly when placed in bone compromised by disease or physiology of the patients. The aim of this study was to fabricate a novel coaxial electrospun polycaprolactone (PCL)/polyvinyl alcohol (PVA) core-sheath nanofiber (NF) blended with both hydroxyapatite nanoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 39 publications
4
71
0
1
Order By: Relevance
“…Moreover, in co-axial spinning the preferred carrier and drug will come in contact only at the point of synthesising nanofiber. It significantly avoids undesired reaction reported to occur between polymer and biomolecules prior to electrospinning [56][57][58]. Later, this core-shell structure was reported to generate using single nozzle electrospinning unit using emulsion input, popularly called as emulsion spinning.…”
Section: Techniques Employed For Loading Drugs Into Electrospun Fibersmentioning
confidence: 99%
“…Moreover, in co-axial spinning the preferred carrier and drug will come in contact only at the point of synthesising nanofiber. It significantly avoids undesired reaction reported to occur between polymer and biomolecules prior to electrospinning [56][57][58]. Later, this core-shell structure was reported to generate using single nozzle electrospinning unit using emulsion input, popularly called as emulsion spinning.…”
Section: Techniques Employed For Loading Drugs Into Electrospun Fibersmentioning
confidence: 99%
“…The drug release characteristic can easily be tailored by modulating the composition of the nanofiber mats, the morphology of nanofibers, the process and the structure. Core-shell (sheath) structure is a useful structure for various types of applications [24,101,[147][148][149]. The combined use of various polymers with different degradation rates can also achieve sequential releases of analgesics [150].…”
Section: Sequential Release Of Different Analgesicsmentioning
confidence: 99%
“…Core-shell structure of the nanofibres slowed the initial release to 45 % in the first day. The mitigation of burst release of a drug from coreshell structured nanofibres has been widely reported in the literature [17,27,43,44]. For example, Park et al [43] fabricated core-shell nanofibres and found that they considerably reduced the burst release of LVF compared to single-component nanofibres.…”
Section: Cumulative Release Of Lvfmentioning
confidence: 99%
“…The burst release could be caused by various reasons such as the presence of the drug on the surface of nanofibres, the degradation rate of the polymer used and the small size of the nanofibres [9][10][11][12][13][14]. One approach used to prolong drug release is to fabricate core-shell nanofibres via core-shell electrospinning with the drug loaded into the core structure [13,[15][16][17]. This prolonged release profile may be due to the drug molecules being trapped in the core section of the fibres [18,19].…”
Section: Introductionmentioning
confidence: 99%